Tetrahydrofuran and natural gas hydrates formation in the presence of various inhibitors - Rojas González, Yenny V. (Curtin University, 2011)
The aim of this thesis is to investigate the formation process of tetrahydrofuran (THF) hydrates and natural gas hydrates, and the effect of kinetic hydrate inhibitors (KHIs) on the formation and growth of these hydrates. Kinetic experiments were conducted in pressure cells in the presence of, or without, KHIs. Interfacial and electrokinetic techniques, including surface tension, Langmuir monolayers and zeta potential, were used to study the adsorption preferences of the inhibitors in two different interfaces, air–liquid and hydrate–liquid. For comparison purposes, selected thermodynamic hydrate inhibitors (THIs) and antiagglomerators (AAs) were investigated in some of the experiments. Sodium chloride was used in experiments where suitable.Four well known KHI polymers, including a terpolymer of N-vinylpyrrolidone, Nvinylcaprolactam and dimethylamino-ethylmethacrylate (Gaffix VC713), poly(Nvinylcaprolactam) (Luvicap EG), and poly(N-vinylpyrrolidone) (PVP40, Mn=40k and PVP360, Mn=360k), were selected for the investigation. A copolymer containing both poly(ethylene oxide) and vinylcaprolactam segments (PEO-VCap) that was developed in the Polymer Research lab in Curtin University, was also investigated. Other chemicals, including methanol (MeOH) and monoethylene glycol (MEG) were used as THIs. Sodium dodecyl sulphate (SDS) was used as an AA.During the THF hydrates kinetic studies, several experimental parameters that are associated with the nucleation and crystal growth process were investigated. The onset of THF hydrates formation, the maximum temperature spike, the magnitude of the temperature rise associated with the hydrate formation, the rate of hydrate formation, and the temperature at the end-point of the hydrate formation, were reported to compare inhibition efficiency. Subcooling was used as the driving force for hydrates formation. The experimental results show that the kinetics of the THF hydrate is affected by the physical chemical environment, which includes the concentration and types of additives used for the inhibition of the hydrates. In comparison to the system containing no inhibitor, there was an increase in subcooling and a reduced onset temperature of hydrates formation when various inhibitors were used.Surface tension studies have demonstrated that the adsorption of KHIs molecules at the air–liquid interface is directly related to its effectiveness inhibiting hydrates. The differences in the fundamental properties of the polymer molecules, such as molecular weight and flexibility of the polymer chain, have an impact on the different adsorption behaviours at the air–liquid interface for all of them. The inhibition efficiency of KHIs was enhanced in the presence of NaCl 3.5 wt% for all the inhibitors, and seemed to be associated to maximum packing of polymer molecules in the monolayer and low surface tension values. The zeta potential results, measured at the THF hydrate–liquid interface, have shown some correspondence with the surface tension results at the air liquid–interface. The compound, with a higher adsorption at the air liquid–interface also showed a higher adsorption at the surface of the THF hydrate. It was observed, that the inhibitor showing the higher adsorption on zeta potential measurements was more effective for reducing the onset temperature of hydrates formation.The kinetic studies have been extended to structure II natural gas hydrates systems, to examine whether the hypothesis proposed for THF hydrates systems were applicable to the gas hydrate systems. Gaffix VC713, Luvicap EG, PVP40 and PEO-VCap were used in this investigation. The gas hydrate formation rate was always slower when KHIs were present in the liquid phase. In all cases, the presence of KHI decreases the temperature of the onset hydrate formation. Polymers, such as PVP40 and PEO-VCap, that showed the worse and the best inhibition performances respectively in THF crystals, exhibited the opposite inhibition performance in gas hydrate crystals. This suggests that a different mechanism of KHIs surface adsorption could be operating on different hydrates surfaces.Overall, the investigation of the kinetics of formation and inhibition on THF hydrates and natural gas hydrates in the presence of KHIs, indicate that the gas hydrate formation rate during gas hydrate formation, is always slower when KHIs are present in the liquid phase. The inhibition mechanism of KHIs in the THF hydrates systems may differ significantly from that of the gas hydrate systems. Adsorption studies, demonstrate that the adsorption of KHIs are directly related to their effectiveness inhibiting hydrates. Surface tension and zeta potential approaches provide valuable information for understanding hydrates formation and inhibition mechanisms.